Gender differences in oral health among prisoners: a cross-sectional study from Taiwan - Yu-Pei Yang; Ho-Tsung Hsin; Bing-Long Wang; Yen-Chun Wang; Pi-Ching Yu; Shi‑Hao Huang; Ren‑Jei Chung; Yao-Ching Huang; Tao-Hsin Tung (BMC, 2023)
Abstract Background The prevalence of oral diseases among Taiwanese prisoners has rarely been investigated. This study aimed to estimate the gender-specific prevalence of oral disease in a sample of Taiwanese prisoners. Methods We included 83,048 participants from the National Health Insurance (NHI) Program. Outcomes were measured using the clinical version of the International Classification of Diseases, Ninth Revision (ICD-9-CM). For prevalence, we provide absolute values and percentages. We also performed a χ2 test to assess sex and age group differences in the percentage of disease in the oral cavity, salivary glands, and jaw. Results The prevalence rate of oral diseases was 25.90%, which was higher than that of the general population. The prevalence of oral diseases in female prisoners was higher than that in male prisoners (p < 0.001), and the prevalence of oral diseases in prisoners aged ≤ 40 was higher than that of prisoners aged > 40. Among all cases of diagnosed oral diseases, the top three diseases were dental hard tissue diseases (13.28%), other cellulitis and abscesses (9.79%), and pruritus and related conditions (2.88%), respectively. The prevalence of various oral diseases in female prisoners was significantly higher than that in male prisoners. Conclusion Oral disease is common among Taiwanese prisoners. Female prisoners had a higher prevalence of oral, salivary gland, and jaw diseases than male prisoners. Therefore, early prevention and appropriate treatment are required and also a need for gender-specific oral disease products given the differences in the prevalence of oral disease among male and female prisoners.